A Supramolecular Copper(II) Complex with an Asymmetric Salamo-Type Ligand: Synthesis and Crystal Structure - Dong, W.-K.; Bai, Y.; Zhang, L.-S.; Dong, X.-Y.; Zhao, M.-M.; Li, G. (Asian Journal of Chemistry, 2014)
A supramolecular mononuclear Cu(II) complex, [CuL], has been synthesized via the complexation of copper(II) acetate monohydrate with 4-chloro-4',6'-dibromo-2,2'-[ethylenediyldioxybis(nitrilomethylidyne)]diphenol (H2L) in methanol/acetone solution and characterized by X-ray diffraction method. X-Ray crystallographic analysis reveals that the Cu(II) atom is tetra-coodinated by N2O2 donor atoms from the asymmetic Salamo-type L2- unit, resulting in an almost regular distorted square-planar geometry. With the help of intermolecular C2-H2A···O2 and C2-H2B···Br1 hydrogen-bonding interactions, a self-assembled 2D-layer supramolecular structure is formed.